The Use of Generic Medications for Glaucoma - Andrew J. Tatham (Journal of Ophthalmology)
The use of generic medicines has grown considerably in recent years providing considerable cost savings. In England, generic items represented 11.7% of prescriptions for glaucoma and ocular hypertension in 2009, increasing to 55.2% of prescriptions in 2018. Generics can be brought to the market quickly and at low cost as manufacturers are not required to repeat animal or clinical research on active ingredients already approved for safety and efficacy. Although there is no regulatory requirement for studies comparing branded and generic eye drops, several randomised crossover studies have been performed comparing branded and generic prostaglandin analogues. While most have shown similar intraocular pressure lowering, studies are of short duration and have not evaluated visual field endpoints. Furthermore, differences in inactive ingredients, pH, viscosity, levels of particulate matter, and degradation over time have been reported. Other potential problems with generic eye drops include differences in bottle design affecting adherence, problems with supply, and the possibility that reduced revenue for innovator companies will lead to reduced investment in new drug development. This article reviews the potential advantages and disadvantages of generic antiglaucoma medications.